Poly[1H-imidazol-3-ium [di-μ-nitrato-sodium]] - Trifa, Chahrazed (International Union of Crystallography, 2013)
In the title compound {(C(3)H(5)N(2))[Na(NO(3))(2)]}(n), the Na(I) ion is coordinated by eight O atoms from three bidentate nitrate anions and two O atoms from two monodentate nitrate anions, displaying a bicapped trigonal–prismatic geometry. The imidazolium cation is essentially planar (r.m.s. deviation for all non-H atoms = 0.0018 Å). In the crystal, the Na(I) ions are connected by bridging nitrate ligands, forming layers parallel to (010). The imidazolium cations are sandwiched between these layers. Weak C—H⋯O hydrogen bonds link the layers into a three-dimensional network. In addtion, π–π interactions between the imidazolium rings [centroid–centroid distance = 3.588 (3) Å] are observed.